The impact of induced drought stress on early seedling parameters and yield traits in tomato (Solanum lycopersicon L.) hybrids - Karthik, G U; Lakshmidevamma, T N; Dileepkumar, M; Mahantesha, BNN; Gollagi, SG; Vilas, DG (Plant Science Today, 2026)
Tomato is one of the most versatile vegetable crops, grown globally under diverse climatic conditions. Abiotic stresses, particularly drought, severely affect tomato productivity, causing yield losses of up to 70 % depending on stress duration and crop growth stage. Present study aimed to breed drought tolerant tomato hybrids by screening 13 parental lines and 30 hybrids along with one hybrid check under induced moisture stress. Early seedling screening using polyethylene glycol (PEG)-6000 revealed a reduction in germination percentage (-1.81 % and -15.60 %), shoot length (-7.28 % and -13.29 %) and seedling vigour index (-5.13 % and -17.55 %) with increasing PEG concentrations (8 % and 16 %) compared to the control. Field evaluation under different irrigation intervals showed significant reduction in plant height (-13.62 % and -28.16 %), total dry matter (-7.03 % and -16.13 %), leaf area (-8.55 % and -19.55 %) and yield (-26.86 % and -50.86 %), while root length (9.30 % and 17.15 %) and proline content (16.58 % and 42.68 %) increased under drought stress conditions (10 days and 20 days irrigation interval). The parental lines, EC-638519, Arka Meghali and Kashi Anupama and hybrids EC-608269 × Kashi Anupama, Arka Meghali × EC-634394 and Arka Saurabh × EC-638519 exhibited superior seedling vigour, yield performance and drought tolerance across early seedling, vegetative and reproductive stages. Molecular screening using 11 simple sequence repeat (SSR) markers resulted in monomorphic banding pattern indicating no detectable variation for these primers among the screened lines. Collectively, the study offers valuable opportunities for breeding hybrids adoptable to extreme drought conditions of marginal areas.